Planning the Retrofitting of Heating Appliances: The HARP Project - Fabio Maria Aprà; Raymond Sterling; Marco Calderoni; Pedro Luis Espejo; Laura Pérez del Olmo; Riccardo Marchetti (Proceedings, 2020)
HARP, or heating appliances retrofit planning, aims at motivating individuals to plan the replacement of their often outdated and fossil-fuel operated heating appliances with more efficient alternatives. The project, which starts its first heating campaign in winter 2020, expects to reach this goal thanks to the creation of a labeling heating system classification through the development of a user-friendly application (HARPa) and the active participation of professionals in the sector.